2021
DOI: 10.3390/biomedicines10010058
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA 92a as a Therapeutic Target for Cardiac Microvascular Dysfunction in Diabetes

Abstract: Microvascular dysfunction is a pathological hallmark of diabetes, and is central to the ethology of diabetes-associated cardiac events. Herein, previous studies have highlighted the role of the vasoactive micro-RNA 92a (miR-92a) in small, as well as large, animal models. In this study, we explore the effects of miR-92a on mouse and human cardiac microvascular endothelial cells (MCMEC, HCMEC), and its underlying molecular mechanisms. Diabetic HCMEC displayed impaired angiogenesis and a pronounced inflammatory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…In addition to the modifications to chromatin, several non-coding RNAs (miRNAs) are implicated in microvascular dysfunction through the targeting of relevant pathways involved in endothelial cell and VSMC damage in diabetes [ 132 ]. A direct link between hyperglycemia and upregulation of miR-92a, associated with inflammatory phenotype and impaired angiogenesis, has been demonstrated in cardiac microvascular ECs from human T2DM patients and in non-diabetic ECs cultured with higher glucose levels [ 133 ]. A very recent study on mouse cardiac microvascular ECs identified a novel molecular mechanism associated with the upregulation of miR-27a-3p.…”
Section: Pathophysiology Of Cmd In Diabetesmentioning
confidence: 99%
“…In addition to the modifications to chromatin, several non-coding RNAs (miRNAs) are implicated in microvascular dysfunction through the targeting of relevant pathways involved in endothelial cell and VSMC damage in diabetes [ 132 ]. A direct link between hyperglycemia and upregulation of miR-92a, associated with inflammatory phenotype and impaired angiogenesis, has been demonstrated in cardiac microvascular ECs from human T2DM patients and in non-diabetic ECs cultured with higher glucose levels [ 133 ]. A very recent study on mouse cardiac microvascular ECs identified a novel molecular mechanism associated with the upregulation of miR-27a-3p.…”
Section: Pathophysiology Of Cmd In Diabetesmentioning
confidence: 99%
“…Similar findings were demonstrated in a large animal model of pigs where this miRNA could protect against ischemia/reperfusion injury [ 77 ]. Furthermore, research has shown that targeting miRNA-92A could serve as a suitable therapeutic approach for addressing diabetes-associated cardiac microvascular dysfunction [ 78 ].…”
Section: Nucleic-acid-based Therapymentioning
confidence: 99%
“…MiRNA-92a can inhibit the expression of A disintegrin and metalloproteinase 10 (ADAM10), Krüpple-like factor2 (KLF2) and Krüpple-like factor4 (KLF4). ADAM10 promotes cell migration, KLF2 and KLF4 are important transcriptional regulators of anti-inflammatory and antioxidant activity ( 114 ). Therefore, cells in the high glucose group with elevated miRNA-92a expression have a significantly reduced ability to migrate and proliferate, and an increased inflammatory response.…”
Section: Role Of Mirna In Cmecs In Diabetesmentioning
confidence: 99%